2014
DOI: 10.1163/22941932-00000044
|View full text |Cite
|
Sign up to set email alerts
|

Wood Anatomy Of Seven Species Of Tachigali (Caesalpinioideae–Leguminosae)

Abstract: This article describes the wood anatomy of seven species of Tachigali Aublet with the aim of identifying 1) diagnostic characters at the species level and 2) anatomical features with potential for future combined morphological and molecular phylogenetic analysis. Tachigali species present fibre dimorphism and can be grouped according to the arrangement of the thin-walled fibres: tangential bands of thin-walled fibres alternating with thick-walled fibres, as in T. duckei and T. vulgaris; wavy bands , as in T. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
8
0
6
Order By: Relevance
“…However, the drying rate of the first clones was higher during the study period and, after 4.5 days of drying, these materials showed lower moisture than C and J clones, a trend that was noted until the end of drying. The clones C and J were 7 years old, and an increase in age results in the production of fibers with greater length and cell wall fraction (PILLAI et al, 2013;MACEDO et al, 2014). This higher cell wall volume reduces wood moisture when saturated and prevents water flow, reducing the drying ra te (KOLLM ANN; CÔTÉ, 1968).…”
Section: Wood Dryingmentioning
confidence: 99%
“…However, the drying rate of the first clones was higher during the study period and, after 4.5 days of drying, these materials showed lower moisture than C and J clones, a trend that was noted until the end of drying. The clones C and J were 7 years old, and an increase in age results in the production of fibers with greater length and cell wall fraction (PILLAI et al, 2013;MACEDO et al, 2014). This higher cell wall volume reduces wood moisture when saturated and prevents water flow, reducing the drying ra te (KOLLM ANN; CÔTÉ, 1968).…”
Section: Wood Dryingmentioning
confidence: 99%
“…On the other hand, the botanical family Fabaceae includes among some of its genera Tachigali Aubl., which comprises 102 forest species, this genus currently includes the former genus Sclerolobium, included for various botanical aspects and also for the anatomy of the wood (MACEDO et al, 2014;MOTA et al, 2017). The Tachigali genus has fast-growing species with high biomass production, it can be used for the recovery of areas degraded by the rapid formation of litter, in reforestation and energy production projects, however, it presents few anatomical studies (REIS et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of wood anatomical studies has been demonstrated in the classification and identification of plants based on certain diagnostic characteristics (Carlquist 2001;Akinloye et al 2012;Macedo et al 2014;Elamin 2018). Wood is identified by examining its anatomical features to determine its species, genera, or family.…”
Section: Introductionmentioning
confidence: 99%